Uji Stabilitas dan Antibakteri Spray Nanoemulsi Ekstrak Bunga Telang (Clitoria Ternatea L.) dengan Variasi Polietilen Glikol (Peg) 400 - Sari, Rizki Tribuana; Ulfa, Ade Maria; Elsyana, Vida (Journal of Islamic Medicine, 2024)
Nanotechnology has been used in drug delivery systems because it can improve drug penetration and absorption. PEG 400 can reduce interfacial tension and create a stable nanoemulsion system that also increase the ability of the active substance to inhibit bacterial growth. The purpose of this study was to identify the stability of spray nanoemulsion preparations of (Clitoria ternatea L.) with variations of PEG 400 and test the antibacterial activity against Staphylococcus epiermidis. Extraction using maceration method then freeze dried the yield obtained was 29.33%. The preparation was carried out physical evaluation test, antibacterial test of disc diffusion method, and stability test. The results of the stability test showed the results of the pH test, spreadability, dry time and viscosity did not experience significant differences (P>0.05). At organoleptic and tests, only F1 was the most stable and preferred preparation. The inhibition zone activity hedonic of spray nanoemulsion preparation with a concentration of 15% amounted to 9.84±0.44 mm, 20% concentration of 10.70±0.65 mm, 25% concentration of concentration was 12.24±0.61 mm. The results of the antibacterial test analyzed using Kruskal-Wallis obtained a significant value of 0.013, which means that there is a significant difference the average value of the bacterial inhibition zone between each treatment group. Spray nanoemulsion of F1 telang flower extract with PEG 400 (15%) showed the most stable physical quality and antibacterial properties.